The bahamas project: effects of a running scalar spectral index on large-scale structure. Issue 1 (20th January 2020) - Stafford, Sam G; McCarthy, Ian G; Crain, Robert A; Salcido, Jaime; Schaye, Joop; Font, Andreea S; Kwan, Juliana; Pfeifer, Simon
ABSTRACT: Recent analyses of the cosmic microwave background (CMB) and the Lyman α forest indicate a mild preference for a deviation from a power-law primordial matter power spectrum (a so-called running). We introduce an extension to the bahamas suite of simulations to explore the effects that a running scalar spectral index has on large-scale structure (LSS), using Planck CMB constraints to initialize the simulations. We focus on five key statistics: (i) the non-linear matter power spectrum (ii) the halo mass function; (iii) the halo two-point autocorrelation function; (iv) total mass halo density profiles; and (v) the halo concentration–mass relation. We find that the matter power spectrum in a Planck -constrained running cosmology is affected on all k -scales examined in this study. These effects on the matter power spectrum should be detectable with upcoming surveys such as LSST and Euclid . A positive running cosmology leads to an increase in the mass of galaxy groups and clusters, with the favoured negative running leading to a decrease in mass of lower mass ($M \lesssim 10^{13} \, M_{\odot }$ ) haloes, but an increase for the most massive ($M \gtrsim 10^{13} \, M_{\odot }$ ) haloes. Changes in the mass are generally confined to $5\rm {-}10{{\ \rm per\ cent}}$ which, while not insignificant, cannot by itself reconcile the claimed tension between the primary CMB and cluster number counts. We also demonstrate that the observed effects on LSS due to a running scalar spectral index are separable from those of baryonic effects to typically a few per cent precision.